2016
DOI: 10.1371/journal.pone.0147528
|View full text |Cite
|
Sign up to set email alerts
|

Reference Charts for Fetal Cerebellar Vermis Height: A Prospective Cross-Sectional Study of 10605 Fetuses

Abstract: ObjectiveTo establish reference charts for fetal cerebellar vermis height in an unselected population.MethodsA prospective cross-sectional study between September 2009 and December 2014 was carried out at ALTAMEDICA Fetal–Maternal Medical Centre, Rome, Italy. Of 25203 fetal biometric measurements, 12167 (48%) measurements of the cerebellar vermis were available. After excluding 1562 (12.8%) measurements, a total of 10605 (87.2%) fetuses were considered and analyzed once only. Parametric and nonparametric quant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
24
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(26 citation statements)
references
References 49 publications
2
24
0
Order By: Relevance
“…11 Work by Cignini et al reported the mean values to increase from 7 mm at 17 weeks to 20 mm at 30 weeks. 8 A strong correlation, r = 0.87, was found between the parameter and gestational age. Vinals et al found a linear correlation of vermal length with gestational age (r > 0.82).…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…11 Work by Cignini et al reported the mean values to increase from 7 mm at 17 weeks to 20 mm at 30 weeks. 8 A strong correlation, r = 0.87, was found between the parameter and gestational age. Vinals et al found a linear correlation of vermal length with gestational age (r > 0.82).…”
Section: Discussionmentioning
confidence: 86%
“…6 Hence measuring the different parameters of vermis and to create a normogram for it would help us to ascertain the abnormalities as well as also benefit the estimation of gestational age. 7,8 Misdiagnosis of vermal dysgenesis by sonography in axial plane may also be prevented with the help of reference values in sagittal vermal diameters that are obtained by autopsy findings. 9 Aim of the present study was to establish an association between the cerebellar parameters and the advancing gestational age.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, reductions in 2D linear measurements of vermian height, width and surface area were seen in the DS cerebellum compared with controls from 21 weeks GA. Whilst not conventionally performed in clinical practice, the fetal cerebellar vermis has successfully been measured on ultrasound 41,42 and it is possible that additional vermis height measures during the fetal anomaly US scan, might increase the non-invasive detection of fetuses with T21 at an earlier time point. Mouse models of DS have implicated the gene Dyrk1A in specific structural and functional cerebellar phenotypes, including reduced volume 43 .…”
Section: Discussionmentioning
confidence: 99%
“…In the case of linear models, there is the concern that extrapolation of results may lead to errors. In addition, ultrasonographic data become scarce in later gestational weeks, and it is more advisable to rely on non-linear models, which have only been proposed in a few papers describing human cerebellar development (Chavez et al 2004;Cignini et al 2016). Based on voxel measurements of mouse cerebellum in MRI, Szulc et al (2015) stated that the non-linear model (polynomial of degree three) was the best fit.…”
Section: Discussionmentioning
confidence: 99%